The effect of reward on social loafing. - Momville, Catherine T
The study was done to find out the effectiveness of reward in eliminating or reducing social loafing. The evaluation potential of the expirementer (social evaluation) was also manipulated to test the possibility that both variables (reward and social evaluation) would be sufficient to eliminate the loafing effect. In a 2X2 experiment that wasconducted, the presentation of reward (absence vs. presence of reward) was crossed with evaluation potential of the expirementer (experiemnt evaluation) vs. no experimenter evaluation). The participants were tested in groups and were given a task to generate uses for a "paper" within 15 minutes. A 2X2 analysis of variance (ANOVA) was used to analyze the data. As the results have revealed the presentation of reward was sufficient to counteract the loafing effect, whether there was an experimenter's evaluation or not. In fact, the presentation of reward was the only motivation needed for social loafing to be eliminated or reduced.